2022
DOI: 10.1111/pai.13849
|View full text |Cite
|
Sign up to set email alerts
|

A pragmatic approach to infant feeding for food allergy prevention

Abstract: Early introduction of allergenic foods into the infant's diet in the first year of life is currently the most promising strategy to prevent food allergy. Around 2015, the publication of the Learning Early About Peanut Allergy (LEAP) randomized controlled trial (RCT) led to a paradigm shift in infant feeding practices, moving away from delayed introduction to deliberate early introduction of common allergenic foods, especially peanut. LEAP showed early and regular consumption of peanut in high-risk infants resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 58 publications
(140 reference statements)
0
12
0
Order By: Relevance
“…We evaluated several factors that have been proposed to be related to the achievement of tolerance in FPIAP in two groups of infants, taking 6 months of age as a cut-off point for early tolerance. Current infant feeding guidelines, including those of WHO and UNICEF, recommend the introduction of complementary foods at 6 months of age, with continued breastfeeding for up to 2 years of age [ 28 , 29 , 30 ]. In breastfed infants, differences in breast milk composition, such as the levels of cytokines or the presence of immunoglobulins, could promote the development of tolerance to antigens present in breast milk [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated several factors that have been proposed to be related to the achievement of tolerance in FPIAP in two groups of infants, taking 6 months of age as a cut-off point for early tolerance. Current infant feeding guidelines, including those of WHO and UNICEF, recommend the introduction of complementary foods at 6 months of age, with continued breastfeeding for up to 2 years of age [ 28 , 29 , 30 ]. In breastfed infants, differences in breast milk composition, such as the levels of cytokines or the presence of immunoglobulins, could promote the development of tolerance to antigens present in breast milk [ 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As one of the most important sources providing the initial bacterial community, human breast milk is the optimal food for infants, while the feeding guidelines vary in different regions 177–179. Previous studies have confirmed the benefits of breast feeding for both mothers and infants 11 178 180 181.…”
Section: Microbial Transmission During and After Deliverymentioning
confidence: 99%
“…Additionally, breast feeding is suggested to alter the maternal metabolic process, greatly decreasing the risk of hypertension, hyperlipidaemia and cardiovascular diseases 186. Although many studies have associated breast milk with a decreased risk of allergies in infants, some of them have indicated that the effectiveness of breast milk in allergy prevention is insufficient and is highly related to the timing and type of introduction of solid food 179 187–189. Such conflicting evidence remains to be further explored.…”
Section: Microbial Transmission During and After Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…This paradigm shift in allergy prevention—away from allergen avoidance toward a tolerance-induction approach [ 8 - 10 ]—challenges both parents and health care professionals (HCPs) as they have to deal with changing information and new evidence that often contradicts previous assumptions. Thus, different knowledge of (changing) guidelines, attitudes, and beliefs about FA may result in heterogeneous counseling practices [ 11 ] and prevention strategies [ 12 ] in pediatricians.…”
Section: Introductionmentioning
confidence: 99%